The Influence of Work Environment and Compensation on Employee Work Spirit at Command Headquarters Marine Corps - Imung Saraswati; Harries Madiistriyatno; Widya Nengsih (Dinasti Publisher, 2026)
The purpose of this study is as follows the influence of the work environment on employee work enthusiasm, the influence of compensation on employee work enthusiasm and the influence of the work environment and compensation simultaneously on employee work enthusiasm at the Marine Corps Command Headquarters (Mako Kormar). The work environment has an effect on employee work enthusiasm, which has been proven empirically. The results of the t-test also prove that compensation has a significant influence on employee work enthusiasm. Work Environment and Compensation simultaneously have a significant influence on Employee Work Morale. Based on the calculated F value, which is greater than the F table with a significance level below 0.05, the work environment and compensation together have a positive and significant relationship with employee morale. The results of this study confirm that morale is not influenced by a single factor, but by a combination of work environment and compensation factors that are managed in an integrated manner in human resource management.